A phase 1 study of dimdazenil to evaluate the pharmacokinetics, food effect and safety in Chinese healthy subjects - Wang, Fei; He, Jingjing; Zhou, Yanling; Ye, Lijun; Li, Bei; Ma, Zhiyuan; Chen, Chunyan; Zhang, Ruoxi; Lin, Zhaocun; Tang, Jinshan; Jin, Zhiping; Jiang, Yu; et al. (Frontiers in Pharmacology, 2023)
Background and objective: As a partial positive allosteric modulator of the gamma-aminobutyric acid A (GABAA) receptor, dimdazenil was used for the treatment of insomnia with the potential to alleviate associated side effects compared to full agonists. The objective of this trial is to assess the safety, tolerability, food effect and pharmacokinetics following single and multiple doses of dimdazenil in Chinese healthy subjects.In this phase 1 trial, 36 healthy subjects aged ≥ 18 years were assigned to receive a single dose of 1.5, 2.5, or 5 mg dimdazenil, with each dose cohort consisting of 12 subjects, and 14 subjects were assigned to receive a multiple 2.5 mg daily dose of dimdazenil for 5 days. Safety, tolerability, and pharmacokinetic characteristics were evaluated. This study was registered at chinadrugtrials.org.cn, number CTR20201978.Results: Of the 50 subjects enrolled and 49 completed the trial, the incidences of treatment-emergent adverse events (AEs) in the single-dose groups of 1.5, 2.5, and 5 mg were 16.7%, 58.3% and 66.7% respectively, while 61.5% in the multiple-dose group. There were no serious AEs, deaths, AEs leading to discontinuation or AEs of requiring clinical intervention in any treatment groups. The most treatment-emergent AEs were dizziness (n=4, 8.2%), hyperuricemia (n=2, 6.1%), upper respiratory tract infection (n=2, 6.1%), diastolic blood pressure decreased (n=2, 6.1%), blood TG increased (n=2, 6.1%) and RBC urine positive (n=2, 6.1%). All AEs were mild-to-moderate and transient, and no severe AEs were documented in any study phase. The PK profile of dimdazenil and its active metabolite Ro46-1927 was linear across 1.5-5 mg oral doses in humans, the median Tmax was in the range of 0.5 to 1.5 h, and the apparent terminal t1/2z ranged from 3.50 to 4.32 h. Taking Dimdazenil with food may delay Tmax and decrease Cmax, without affecting the total exposure (AUC).No relevant accumulations of dimdazenil and Ro 46-1927 were observed in multiple-dose group.Conclusions: Dimdazenil was generally well tolerated in healthy Chinese subjects after single and 5 day-multiple dosing. The pharmacokinetic properties of dimdazenil are compatible with a drug for the treatment of insomnia.